BRITISH COLONIAL PUNISHMENTS IN NORTHERN NIGERIA: A STUDY OF NATIVE AUTHORITY PRISON AND CRIME CONTROL IN IDAH DISTRICT, 1929-1945 - OLASUNKANMI VICTOR ASAJU; YAHAYA YUSUF (International Studies Journal)
This paper examines British colonial punishments in northern Nigeria, with a specific focus on the Native Authority Prison in Idah district. Prior to the advent of British administration, Idah was renowned for its indigenous methods of punishments that were rooted in its customs and traditions. These indigenous punishments never alienated offenders from their community, and the idea of incarceration without timely prosecution and integration of offenders was unheard of in the area. However, pre-colonial punishment in Idah was not only predicated on peace-building, but it also had the potential to transform offenders after the process of justice administration and dispensation. While, this was peculiar to those who committed minor offenses, perpetrators of serious crimes such as murder, homicide, and arson were immediately made to face the consequences of their actions, which were mostly total banishment from both the immediate community and adjoining settlements. The study argues that, beyond the fact that the Native Authority Prison was built to sustain colonial labour, which was a common phenomenon at that time, the Native Authority Prison created a new form of asymmetrical power relations in Idah district, a society which had previously been paternalistic in nature. The paper employs the qualitative research methods alongside the exploration of historical primary sources such as oral interviews and archival data as well as secondary sources which include both published and unpublished literature such as books, journal articles and processed internet materials.